2000
DOI: 10.1103/physrevb.62.16040
|View full text |Cite
|
Sign up to set email alerts
|

Local electronic properties of carbon nanotube heterojunctions

Abstract: Local electronic properties of metallic-semiconducting carbon nanotube heterostructures are investigated by studying the behavior of the one-electron local density of states ͑LDOS͒ along the tubes. We determine how these properties change from the metallic to the semiconducting side of a nanotube junction. We show that Friedel oscillations may not always be evident on the metallic side, and we found clear exponential decay of the LDOS on the semiconducting side. The exponential rates of decay as well as the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…The Green's functions of the leads are calculated using recursive methods, largely explored in different carbon systems [3,38,39], while for the central system, circular real-renormalization procedures [40] are employed. As expected, due to the translation symmetry on the y-direction, the conductances of such fold-deformed ribbons are still marked by a sequence of plateaux as in the case of pristine graphene nanoribbons, but with energy shifts determined by the strain parameters of the theoretical model, as seen in Fig.…”
Section: Structures and Modelmentioning
confidence: 99%
“…The Green's functions of the leads are calculated using recursive methods, largely explored in different carbon systems [3,38,39], while for the central system, circular real-renormalization procedures [40] are employed. As expected, due to the translation symmetry on the y-direction, the conductances of such fold-deformed ribbons are still marked by a sequence of plateaux as in the case of pristine graphene nanoribbons, but with energy shifts determined by the strain parameters of the theoretical model, as seen in Fig.…”
Section: Structures and Modelmentioning
confidence: 99%
“…The electronic properties of the SWNT IMJs have been the subject of an increasing number of experimental and theoretical studies [11][12] since 1995. Chico et al [13][14] indicated that a pentagon-heptagon pair with symmetry axis nonparallel to the tube axis could change the nanotube helicity by one unit from (n,m) to (n+1,m-1).…”
Section: Introductionmentioning
confidence: 99%
“…11 Sufficiently far from the junction, the one-electron local density of states ͑LDOS͒ at the Fermi energy (E F ) vanishes exponentially on the semiconducting side, but oscillates around the bulk-limit value in the metallic side. Oscillations of the LDOS along the tube axis were experimentally observed in very short structures, 12 but they still need to be observed in long nanotubes.…”
Section: Introductionmentioning
confidence: 99%